2023
DOI: 10.4103/ajps.ajps_90_22
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Demographics, Clinical Presentation and Surgical Procedures Performed for the Appendico-Umbilical Fistula for the PasQAt 100 Years

Abstract: The persistent vitellointestinal duct (PVID) is the rarest of all the vitelline duct anomalies. The enteric end of the vitelline duct mostly connects to the terminal ileum. The appendico-umbilical fistula (appendiceal-umbilical fistula) in which the proximal end of the vitelline duct connects to the appendix is a rare clinical entity. This systematic literature review was carried out to review the demographics, clinical characteristics and operative procedures executed for the appendico-umbilical fistula. Lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…A recent systematic literature review of the past 50 years (1971-2021), comprised of n=280 infants, treated for the PVID, found/revealed that 72% of cases were diagnosed and treated during the neonatal period. Further review revealed that 90% of the infants were treated for PVID during the first 3 months of their life [6]. The literature review further supports that three-fourths of PVID cases were boys [6,10].…”
Section: Ghritlahareymentioning
confidence: 63%
See 4 more Smart Citations
“…A recent systematic literature review of the past 50 years (1971-2021), comprised of n=280 infants, treated for the PVID, found/revealed that 72% of cases were diagnosed and treated during the neonatal period. Further review revealed that 90% of the infants were treated for PVID during the first 3 months of their life [6]. The literature review further supports that three-fourths of PVID cases were boys [6,10].…”
Section: Ghritlahareymentioning
confidence: 63%
“…Further review revealed that 90% of the infants were treated for PVID during the first 3 months of their life [6]. The literature review further supports that three-fourths of PVID cases were boys [6,10].…”
Section: Ghritlahareymentioning
confidence: 63%
See 3 more Smart Citations